2017
DOI: 10.1038/ncomms15128
|View full text |Cite
|
Sign up to set email alerts
|

Programming mRNA decay to modulate synthetic circuit resource allocation

Abstract: Synthetic circuits embedded in host cells compete with cellular processes for limited intracellular resources. Here we show how funnelling of cellular resources, after global transcriptome degradation by the sequence-dependent endoribonuclease MazF, to a synthetic circuit can increase production. Target genes are protected from MazF activity by recoding the gene sequence to eliminate recognition sites, while preserving the amino acid sequence. The expression of a protected fluorescent reporter and flux of a hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 66 publications
0
45
0
Order By: Relevance
“…Yet, unintended interactions arising from synthetic TX devices remains a problem, and there currently does not exist a sufficiently large library of orthogonal ribosomes to assign an independent resource to each TX device. In [40], Venturelli et al engineered a sequencespecific ribonuclease to cleave certain host cell transcripts, thus diverting resources to synthetic proteins to increase productivity of synthetic metabolic pathways. Conversely, Ceroni et al constructed a dCas9-based feedback controller that represses the synthetic circuit when its resource demand is high, thus reallocating resources to maintain constant host cell growth [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, unintended interactions arising from synthetic TX devices remains a problem, and there currently does not exist a sufficiently large library of orthogonal ribosomes to assign an independent resource to each TX device. In [40], Venturelli et al engineered a sequencespecific ribonuclease to cleave certain host cell transcripts, thus diverting resources to synthetic proteins to increase productivity of synthetic metabolic pathways. Conversely, Ceroni et al constructed a dCas9-based feedback controller that represses the synthetic circuit when its resource demand is high, thus reallocating resources to maintain constant host cell growth [41].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, unintended interactions arising from synthetic TX devices remains a problem, and there currently does not exist a sufficiently large library of orthogonal ribosomes to assign an independent resource to each TX device. In [37], Venturelli et al engineered a sequence-specific ribonuclease to cleave certain host cell transcripts, thus diverting resources to synthetic proteins to increase productivity of synthetic metabolic pathways. In [25], Darlington et al partitioned the ribosome pool into synthetic circuit-specific and host-specific ribosomes using orthogonal rRNAs, and implemented a feedback controller to increase the portion of synthetic circuit-specific ribosomes when more are demanded.…”
Section: Discussionmentioning
confidence: 99%
“…Models incorporating circuit-host competition effects can predict synthetic gene behaviors better (Liao et al, 2017). Reallocating the cellular translational resources by introducing the endoribonuclease MazF circuit can significantly enhance exogenous enzyme expression to promote metabolite production (Venturelli et al, 2017). Utilizing synthetic miRNA and its competitive binding RNA sponges, a RNAbased AND gate circuit was designed for selectively triggering T cell-mediated killing of cancer cells (Nissim et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Programming mRNA decay to modulate synthetic circuit resource allocation [39] Using the MazF sequence-dependent endonuclease, the authors demonstrated that protecting the mRNA of synthetic constructs against MazF degradation leads to improved productivity and titer of gluconate due to translational resource reallocation.…”
Section: (••)mentioning
confidence: 99%